(untitled) (e-Journal of Linguistics, 2025)
This study employs a semantic-pragmatic-sociopragmatic framework to analyze five Indonesian memes, exploring their role as cultural artifacts that navigate modern societal tensions. Through qualitative multimodal discourse analysis, the research examines how memes blend linguistic creativity, humor, and visual symbolism to critique issues such as academic pressure, procrastination, and cultural apathy. Key findings reveal that memes rely on semantic contrasts (e.g., literal vs. figurative meanings) to generate irony, pragmatic strategies like hyperbole and satire to subvert institutional norms, and sociopragmatic resonance to reflect collective experiences. Examples include the juxtaposition of Javanese cultural values with universal symbols ("Raurus") and the use of dark humor to criticize educational systems ("Student in ICU"). The study highlights memes’ dual function as tools for communal solidarity and platforms for subtle social critique, emphasizing their reliance on local dialects (e.g., "gini pak") and digital vernacular. Broader implications underscore memes’ significance in democratizing discourse and shaping digital literacy. Academically, the tripartite framework offers a robust methodology for decoding digital communication, while technological applications call for culturally adaptive AI to address nuances in sarcasm and context. Societally, memes challenge rigid definitions of success and productivity, advocating for empathy in an era of digital fragmentation. This research positions memes as vital, dynamic reflections of contemporary identity and resistance, bridging individual expression with collective cultural narratives.